Pengaruh Pembelajaran Student Team Achievement Division Menggunakan Media Puzzle pada Mata Pelajaran IPS Materi Kegiatan Perdagangan Serta Pengaruhnya Terhadap Indonesia dan Asean Terhadap Hasil Belajar Siswa Kelas VIII SMP Nurul Hadina - Tambunan, Irma Chairani; Imsar, Imsar (Jurnal Manajemen Akuntansi (JUMSI), 2023)
This research was conducted in order to see the effect of student team achievement division learning using puzzle media on social studies subjects on trade activities and their influence on Indonesia and Asean on student learning outcomes in class VIII SMP Nurul Hadina. This research is a quantitative study, emphasizing data processing in numerical form (numbers) and data processing techniques in this study using the SPSS version 21 application. The sample in this study was class VII SMP Nurul Hadina as the population. This research took place in class VIII Al-Hakim and VIII Al-Wassi'. The sampling technique used was cluster random sampling, the Al-Wassi' class served as the experimental class, while the Al-Hakim class served as the control class. This research data collection used a test instrument totaling 20 questions which were distributed to students. The data were then analyzed using descriptive statistical analysis and inferential statistics (t-test). From the research that has been done it proves that there is a significant influence on social studies learning outcomes of students between the control and experimental classes. The average value of the experimental class was 82.00 while the control class was 61.33. And data analysis using the t-test obtained T_count = 36.874 greater than T_table = 1.671 with a significant level of 0.05. In accordance with the hypothesis testing, it proves that there is a significant influence on the implementation of student team achievement division learning using puzzle media in the social studies subject matter of trading activities and its influence on Indonesia and Asean on the learning outcomes of class VIII students of SMP Nurul Hadina.